Implementation of Microservices Architecture in Learning Management System E-Course Using Web Service Method - Dahri, Fachru; Hanafi, Andi Marwan El; Handoko, Divi; Wulan, Nur (Sinkron : jurnal dan penelitian teknik informatika, 2021)
Building a learning system using the Learning Management System is already too much but there are many problems that make people think about using it because it is difficult to maintain the system, so to build a system takes a lot of time because the basis for developing the system is monolith-based and difficult to develop if the system development team grows or change. Learning Management System needs to be implemented for easy access to learning because online learning is very important to be a good alternative. From these problems led to the idea to create a Learning Management System in which it can solve services and communicate between services to facilitate efficient development. This study aims to apply the Web Service Implementation Methodology used in building a Learning Management System for an E-Course that facilitates online learning by implementing web services. To perform inter-service solving the methodology used in making this application is the web service method which is implemented on the microservices architecture. Programming languages for differentiating services are PHP and JavaScript. For the user interface, ReactJS is used as the API data manager for each service and the database uses MySQL. This application will later be used as a medium to facilitate online learning, there are members (users) as student actors and admins to manage mentor and course data that will be displayed.